Molecular cloning and expression characteristics of ghrl and ghsr genes in bighead carp (Hypophthalmichthys nobilis) - Pan Wang; Jianjun Fu; Mingkun Luo; Xiulan Shi; Wenbin Zhu; Lanmei Wang; Shichang Shu; Zaijie Dong (Aquaculture and Fisheries)
Ghrelin (ghrl) and its receptor gene ghsr (growth hormone secretagogue receptor) regulate numerous physiological functions, including growth hormone secretion and food intake. In the present study, we investigated the sequences and expression characteristics of these two genes in bighead carp (Hypophthalmichthys nobilis). The ghrl and ghsr genes encoded 106 and 346 amino acids, respectively, and were 1208 bp and 2239 bp in length. Early blastocysts exhibited the highest levels of ghrl and ghsr expression throughout early development (P < 0.01). The gut exhibited the highest levels of ghrl expression, whereas significantly higher levels of ghsr (P < 0.01) were detected in the brain. Significantly higher levels of ghrl and ghsr expression were detected in the intestine and muscle in summer compared to the levels in winter (P < 0.05). Furthermore, the significantly higher levels of ghrl and ghsr expression were detected in the muscle of individuals with big size compared to the levels of individuals with small size (P < 0.05). In situ hybridization analyses revealed that the intestine ghrl expression signals were more pronounced than intestinal ghsr expression signals, whereas the ghsr expression signals were more intense than those of ghrl in brain tissues. Finally, the co-expression patterns of related genes in the growth hormone synthesis, secretion, and action pathway (ko04935) and the cAMP signaling pathway (ko04024) indicated that ghrl and ghsr potentially regulate feeding and associated energy metabolism activities in bighead carp, in addition to influencing growth performance.